Influence of two-electrode montages on the level-specific (LS) CE-Chirp auditory brainstem response (ABR) at multiple intensity levels - Dzulkarnain, Ahmad Aidil Arafat; Noor Ibrahim, Siti Hajra Mu’minah; Anuar, Nur Farah Aida; Abdullah, Siti Aisyah; Tengku Zam Zam, Tengku Zulaila Hasma; Rahmat, Sarah; Mohd Ruzai, Muhammad Amar (Taylor and Francis, 2017)
Objective: To investigate the influence of two different electrode montages (ipsilateral: reference to mastoid and vertical: reference to nape of neck) to the ABR results recorded using a level-specific (LS)-CE-Chirp® in normally hearing subjects at multiple intensities levels. Design: Quasi-experimental and repeated measure study designs were applied in this study. Two different stopping criteria were used, (1) a fixed-signal averaging 4000 sweeps and, (2) a minimum quality indicator of Fmp = 3.1 with a minimum of 800 sweeps. Study sample: Twenty-nine normally hearing adults (18 females, 11 male) participated. Results: Wave V amplitudes were significantly larger in the LS CE-Chirp® recorded from the vertical montage than the ipsilateral montage. Waves I and III amplitudes were significantly larger from the ipsilateral LS CE-Chirp® than from the other montages and stimulus combinations. The differences in the quality of the ABR recording between the vertical and ipsilateral montages were marginal. Conclusions: Overall, the result suggested that the vertical LS CE-Chirp® ABR had a high potential for a threshold-seeking application, because it produced a higher wave V amplitude. The Ipsilateral LS CE-Chirp® ABR, on the other hand, might also have a high potential for the site of lesion application, because it produced larger waves I and III amplitudes.